Frontal Cognitive Function and Memory in Parkinson’s Disease: Toward a Distinction between Prospective and Declarative Memory Impairments? - A. I. Tröster; J. A. Fields (Behavioural Neurology)
Memory dysfunction is a frequent concomitant of Parkinson's disease (PD). Historically, two classes of hypotheses, focusing on different cognitive mechanisms, have been advanced to explain this memory impairment: one postulating retrieval deficits (common to several neurodegenerative disorders involving the basal ganglia), and the other postulating frontally mediated executive deficits as fundamental to memory impairment. After outlining empirical support for the retrieval deficit hypothesis, research on the more recent “frontal executive deficit hypothesis” is reviewed, and major challenges to this hypothesis are identified. It is concluded that the frontal executive deficit hypothesis cannot adequately account for all memory impairments in PD, and that a more parsimonious theoretical account might invoke a distinction between prospective and declarative memory impairments. It is suggested that there may be three subgroups of PD patients: one demonstrating prospective memory dysfunction only, one with declarative memory dysfunction only, and one with both prospective and declarative memory dysfunction. Consequently, PD might provide a useful model within which to investigate the relationship between prospective and declarative memory.